Minimally invasive complete mesocolic excision and central vascular ligation (CME/CVL) for right colon cancer - Ho, Ming Li Leonard (J Gastrointest Oncol, 2020)
Total mesorectal excision (TME) is the standard of care in rectal cancer surgery. Complete mesocolic excision and central vascular ligation (CME and CVL) are surgical concepts that are extrapolated from the principles of TME. Increasingly adopted by surgical units worldwide, laparoscopic CME/CVL for right sided colon cancer is a challenging procedure that requires meticulous dissection by the surgeon and detailed knowledge of the colonic vascular anatomy. This review article addresses the main issues pertaining to this surgical technique and also discusses steps on how to perform this operation safely.